Aplikasi Marketing Event bagi UMKM Berbasis Android - Azizah, Azizah; Jumi, Jumi; Nugroho, Bayu Setyo; S, Sri Marhaeni (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Access information about marketing events, MSMEs must search through the internet. Looking on the internet, of course, you must be observant and patient in finding the desired marketing event, such as looking for an exhibition/Bazaar that is close to the location of MSMEs so that it is easy to reach and does not require a lot of transportation costs, looking for workshops on certain topics, looking for exhibitions/bazaars that match the products sold, and so on. These various search criteria are what need extra effort for MSMEs to find them. Information about marketing events obtained through the internet is also not necessarily accurate, because now increasingly widespread fraud to the public about the procurement of bazaars in offices, malls and crowded places. Make it easier for MSMEs and Event marketing organizers to find or provide information related to an event, an android-based application that is easy to download and access is needed to facilitate it. This application contains a database of marketing events obtained from various meida and has been checked in advance to ensure the truth so as to minimize MSMEs from fraud under the guise of marketing events. This application has a search feature location marketing event using haversine formula and data search marketing event according to keywords entered by the user, such as searching for workshops with a particular topic, with the Boyer Moore method. The event marketing application provides benefits to MSME actors by providing various information about the exhibition or bazaar activities that will be held so as to encourage MSMEs to more actively participate in these activities. The activeness of MSME actors in various marketing events is expected to increase sales and expand MSME relationships that will provide a positive climate in the business world